Respuesta :
Here are the steps that you use to solve this equation:
Distribute 1.2 to 6.3 and –7x .
Combine 3.5 and 7.56.
Subtract 11.06 from both sides.
REALLY HOPE THIS HELPS :)
Distribute 1.2 to 6.3 and –7x .
Combine 3.5 and 7.56.
Subtract 11.06 from both sides.
REALLY HOPE THIS HELPS :)
Answer:
- Distribute 1.2 to 6.3 and –7x.
- Combine 3.5 and 7.56.
- Subtract 11.06 from both sides.
Step-by-step explanation:
We have the expression [tex]3.5 + 1.2(6.3 -7x) = 9.38[/tex], we have to solve for x, and we are going to solve step by step.
1. We can distribute 1.2 to 6.3 and -7x, this is:
[tex]3.5 + 1.2(6.3 -7x) = 9.38\\3.5+(1.2)*(6.3)+(1.2)*(-7x)=9.38\\3.5+7.56-8.4x=9.38[/tex]
2. We can combine 3.5 and 7.56
[tex]3.5+7.56-8.4x=9.38\\11.06-8.4x=9.38[/tex]
3. We can subtract 11.06 from both sides of the equation:
[tex]11.06-8.4x=9.38\\11.06-8.4x-11.06=9.38-11.06\\-8.4x=-1.68[/tex]
4. For the last step we are going to divide both sides in (-8.4):
[tex]\frac{-8.4x}{(-8.4)}=\frac{-1.68}{(-8.4)} \\\\x=0.2[/tex]
We obtain that x=0.2
And the steps we use from the list are:
- Distribute 1.2 to 6.3 and –7x.
- Combine 3.5 and 7.56.
- Subtract 11.06 from both sides.